Multiorgan Dysfunction Related to Kratom Ingestion. Issue 8 (25th August 2021) - Khan, Muhammad Zarrar; Saleh, Mohannad Abou; Alkhayyat, Motasem; Roberts, Daniel E.; Lindenmeyer, Christina C.
ABSTRACT: Consumption of herbal supplements has been linked to multiorgan toxicities. Kratom is an herbal extract that has gained popularity for its analgesic and psychotropic properties. Several cases of kratom-induced liver injury have been reported, but data on multiorgan involvement remain scarce. We present the case of a 37-year-old woman who developed a mixed hepatocellular and cholestatic pattern of acute liver injury, acute kidney injury, and pancolitis after prolonged use of kratom-containing herbal supplements.